The Protective Effect of Sesame Oil on the Male Reproductive System in Male Rabbits Exposed to the Experimental Hyperlipidemia - Omar A. Kanosh (Journal of Global Pharma Technology, 2019)
The current study aimed to investigate the protective effect of sesame oil on the male reproductive system in male rabbits exposed with experimental hyperlipidemia. The study was conducted at the Animal House of the College of Education for Pure Sciences / University of Tikrit and included 15 rabbits of New Zealand rabbits and distributed to 3 groups and each group consisting of 5 animals. First group) Control group (: Treated with standard mixture of food and regular drinking water. Second group: were treated with standard mixture of food and added cholesterol (1% g / kg) .Third group: treated with a standard mixture of food and added cholesterol at a concentration of (1% g / kg) and sesame oil (1 ml / kg). The experiment lasted for 21 days. The results showed a significant decrease in concentrations of Cholesterol, HDL, LDL, VLDL and MDA in cholesterol and sesame oil groups and significant increase in GSH concentration compared with the cholesterol group. The results showed that hypercholesterolemia resulted in a significant decrease in the level of sperm and natural and live sperm and a significant increase in the level of deformed and dead sperm, while treatment with sesame seed oil showed a significant increase in the ratio of natural and live sperm and vitality and a significant decrease in the proportion of dead and deformed sperm. From that we conclude that sesame seed oil has excellent role on the prevention of the negative effects of hypercholesterolemia on the properties and vitality of the sperms.Keywords: Hypercholesterolemia, Sesame oil. Lipid profile, Glutathione, Malondialdehyde.